CALCULATION OF THE RESISTANCE OF A LINEAR-STEPPING PLUG WITH A CUT SPHERICAL DISK - Rashidov Nurbek son of Shermamat; Temirov Isroil Gulomovich (Ta’lim innovatsiyasi va integratsiyasi, 2026)
Abstract: The total traction resistance of linear-step plow with truncated spherical disc was determined as the sum of the traction resistances of disc blades, housings, soil deepeners and truncated spherical discs.